ANALISIS PEMAHAMAN KONSEP MATEMATIKA SISWA PADA MATERI PERKALIAN DIKELAS II SDN 11 SITIUNG - Ratnawati; Suci Rahma Putri; Zostarvia Agusti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The background problem of this research is the low mathematics scores of students and there are still many students who experience difficulties in completing multiplication calculation operations. This research aims to identify class II students' understanding of Mathematics concepts in multiplication material, and to determine the difficulties experienced by class II students at SDN 11 Sitiung in completing multiplication calculation operations. The type of research used is descriptive qualitative. The data collection techniques used in this research are observation, interviews and documentation. Data collection uses test and interview methods. The research subjects were 6 students, each consisting of 2 students classified as high, medium and low ability, taken from 19 class II students at SDN 11 Sitiung. The instrument used in this research is test questions containing multiplication calculation operation problems. The indicators used to describe students' understanding of mathematical concepts are using the indicators proposed by Kilpatrik, namely: 1) restating the concepts that have been learned, 2) classifying objects based on mathematical concepts, and 3) presenting concepts in various representations. The data analysis techniques in this research are data collection, data reduction, data presentation, and drawing conclusions. The results of the research showed that the achievement of understanding mathematical concepts was the first indicator, 3 out of 6 students had achieved the achievement of understanding the concept. In the second indicator, only 2 out of 6 students classified objects based on mathematical concepts. In the third indicator, 6 out of 6 students were able to present concepts in various representations.